THEORETICAL KNOWLEDGE OF COGNITIVE LINGUISTICS - Davurova Umida Jo'raqul qizi. (Scholar Express Journal, 2023)
One of the important branches of linguistics is cognitive linguistics. This article discusses the uniqueness of cognitive linguistics, its problems, and the opinions of scientists.
Keywords: cognitive linguistics; psychological approach